Autologous stem cell transplantation in newly diagnosed multiple myeloma patients with severe renal failure requiring hemodialysis. A single-center experience - Yu. I. Kliuchagina; P. A. Zeynalova; E. G. Gromova; T. T. Valiev (Онкогематология)
Background. Renal failure (RF) is unfavorable prognostic factor for the multiple myeloma (MM) patients, negatively affecting overall survival. High-dose chemotherapy followed by autologous hematopoietic stem cell transplantation (auto-HSCT) is associated with an increased risk of HSCT-related complications and mortality, which may limit its implementation in MM patients with RF, especially in patients with severe RF requiring hemodialysis.Aim. To analyze the effectiveness and adverse events of high-dose chemotherapy followed by auto-HSCT in newly diagnosed MM patients with severe RF requiring hemodialysis.Materials and methods. We analyzed the data of 7 newly diagnosed MM patients with severe RF requiring hemodialysis, who received auto-HSCT.Results. Complete remission achieved 2 (28.6 %) patients, very good partial remission – 4 (57.1 %) patients, partial remission – 1 (14.3 %) patient on the 100th day after auto-HSCT. Complete renal response achieved 6 (85.7 %) patients, 1 (14.3 %) patient remained a minimal renal response. Auto-HSCT led to an improvement in both hematological and renal responses in 1 (14.3 %) patient, hematological response – in 2 (28.6 %) patients. With a median follow-up of 19 months, median progression-free survival and overall survival were 43 and 81 months, respectively. In the early post-transplant period, febrile neutropenia (71.4 %) and grade III–IV mucositis (71.4 %) were most often diagnosed. In the study group of patients, there was no auto-HSCT-related mortality.Conclusion. Auto-HSCT is an effective and safe method of treating newly diagnosed MM patients with severe RF requiring hemodialysis.